Cardio-metabolic health and sleep quality in adults at risk for Type 2 Diabetes using the Fos Biomedical Non-Transdermal Patch System via photo-biomodulation: A randomized, placebo-controlled crossover trial - Valentine Y. Njike; Rockiy G. Ayettey; Judith A. Treu; Beth Patton Comerford; Maureen Onuigbo (Contemporary Clinical Trials Communications)
Background: The impact of the Fos Biomedical non-transdermal patch system (NTPS) that stimulates the skin with low light levels to generate photo-biomodulation (PBM) effects on cardio-metabolic health and sleep quality is unclear. We examined the impact of FBPS compared with placebo on cardio-metabolic risk and sleep quality in persons at risk for type 2 diabetes mellitus (T2DM). Methods: The study was a randomized, controlled, double-blind, crossover trial of 39 adults (mean age 64.4 years; 28 women, 11 men; 38 Caucasians, 1 African American) at risk for T2DM assigned to one of two possible sequence permutations of two treatments (Fos Biomedical NTPS and placebo), with an 8-week washout period. Fos Biomedical NTPSs are designed to stimulate the skin with low light levels to produce PBM effects. Participants were instructed to apply the active or placebo patches above and below the belly button for 12 h each day for 12 weeks. Primary outcome measure was glycated hemoglobin (HbA1c). Secondary outcome measures included insulin sensitivity, lipid profile, blood pressure, body composition, C-reactive protein, endothelial function, and sleep quality. Results: Compared with the placebo, the Fos Biomedical NTPS did not improve glycemic control: HbA1c (0.1 ± 0.2 % vs. 0.1 ± 0.2 %; p = 0.5154). Compared with placebo, Fos Biomedical NTPS reduced endothelial function (−1.7 ± 12.1 % vs. 3.9 ± 10.0 %; p = 0.0344) while other markers of cardiovascular risk (i.e., body composition, blood pressure, lipid profile, and inflammatory biomarker) and sleep quality were unaffected (p > 0.05). Conclusions: Photo-biomodulation generated from Fos Biomedical NTPS did not improve biomarkers of cardio-metabolic risk and sleep quality among those at risk for T2DM. Clinical trial registration number: NCT05628597.